Sleep disturbance and social reward processing as characteristics linking minority victimization and suicidal ideation in youth - Seah, T. H. Stanley; Eckstrand, Kristen L.; Gupta, Tina; Jensen, Lily C. X.; Brodnick, Zachary M.; Horter, Chloe M.; Gregory, Alice M.; Franzen, Peter L.; Marshal, Michael P.; Forbes, Erika E. (Frontiers in Neuroscience, 2025)
Adolescence is characterized by heightened sleep disturbances (e.g., poor sleep quality and irregular/insufficient sleep) and sensitivity to social feedback that may exacerbate suicidal ideation (SI). Victimization experiences (e.g., bullying, humiliation) can contribute to sleep disturbances and SI, particularly among minoritized youth (e.g., sexual/gender, racial/ethnic minorities). However, sensitivity to social reward, despite social challenges, may buffer against the effects of victimization on sleep and SI. In a diverse sample of youth at varying suicide risk, we examined sleep disturbance as a mediator of victimization and SI, and if neural response to social reward moderated the link between victimization and sleep disturbance. Ninety eight youth (14–22 years old; 50% sexual and/or racial/ethnic minority) with varying SI severity provided self-report data on past-six-month identity-related victimization, past-week sleep disturbance, and past-month SI. Seventy four youth completed an fMRI task involving receipt of social feedback. Region-of-interest analyses examined ventral striatum (VS) activity during positive feedback. Mediation and moderation effects were examined using linear regressions. Sleep disturbance mediated the association between identity-related victimization and SI: higher victimization was associated with worse sleep disturbance, predicting more severe SI. Moderation analyses revealed a positive association between victimization and sleep disturbance at lower but not higher levels of VS response to social reward. Sleep disturbance occurring in the context of social stress heightens vulnerability for SI, particularly among minoritized youth. Greater neural sensitivity to social reward buffers against the effects of victimization on sleep, with implications for mitigating SI. Findings suggest potential mechanisms and individual difference factors underlying minority health disparities.